Association between Balance Confidence and Risk of Fall among Geriatric Population - Kaynat, Farwa; Nazir, Soyba; Kumail, Syed Muhammad; Ramal, Shiza; Arooj, Ateeb; Farooq, Anum (Indus Journal of Bioscience Research, 2025)
Background: Falls among the geriatric population are a leading cause of injury and reduced quality of life. Psychological factors, such as balance confidence, play a critical role in fall prevention, yet their relationship with fall risk remains underexplored. Objective: This study aimed to evaluate the association between balance confidence and the risk of falls in older adults. Methods: A cross-sectional study was conducted involving 245 participants aged 65–90 years from three old-age homes in Lahore, Pakistan. Balance confidence was assessed using the Activities-Specific Balance Confidence (ABC) Scale, while fear of falling (FoF) was measured using the Falls Efficacy Scale-International (FES-I). Data were analyzed using Pearson’s correlation, independent t-tests, and multivariate regression analysis in SPSS version 25. Ethical approval and informed consent were obtained. Results: The mean ABC score was 57.6 ± 13.4%, and the mean FES-I score was 31.4 ± 6.8. A significant negative correlation was found between ABC and FES-I scores (r = -0.72, p < 0.001). Females reported lower balance confidence (54.1 ± 12.8) and higher FoF (33.1 ± 7.2) than males (p < 0.01). Prior fall history and higher FES-I scores significantly predicted lower ABC scores (p < 0.05). Conclusion: Higher balance confidence was associated with a reduced risk of falling. Interventions targeting balance confidence are crucial for fall prevention in older adults.